Internet connectivity disruption in CV (Cabo Verde) - Voidly (2026)
CRITICAL severity disruption detected in Cabo Verde. Confidence: 67%. Data sourced from IODA.
Network Disruption Incident ID: CV-2026-0014
Keywords: internet disruption; CV; disruption; critical